Does critical swimming velocity represent exercise intensity at maximal lactate steady state? - Wakayoshi, K.; Yoshida, T.; Moritani, T. (Medicine & Science in Sports & Exercise, 1993)
It was found that a maximum swimming pace somewhere between 200 m and 400 m pace is the level of maximal lactate steady state (MLSS). A conservative estimate would be 400 m pace although others (e.g., ICAR) suggest that pace would be more of a lactate tolerance pace than MLSS.